Capsaicin Improves Glucose Tolerance and Insulin Sensitivity Through Modulation of the Gut Microbiota‐Bile Acid‐FXR Axis in Type 2 Diabetic db/db Mice. Issue 23 (25th September 2019) - Hui, Suocheng; Liu, Yang; Chen, Mengting; Wang, Xiaolan; Lang, Hedong; Zhou, Min; Yi, Long; Mi, Mantian
Abstract : Scope: Previous studies have linked dietary capsaicin (CAP) intake to improved glucose homeostasis and insulin sensitivity. However, the underlying mechanisms remain unclear. Methods and results: Type 2 diabetic db/db mice are fed a chow diet with or without CAP treatment for 8 weeks. CAP administration markedly improves glucose tolerance and insulin sensitivity through decreasing gluconeogenesis and increasing glycogen synthesis in the liver. Furthermore, CAP inhibits the increase in abundance of the genus Lactobacillus and its bile salt hydrolase (BSH) activity compared with levels in chow‐fed mice, thereby leading to the accumulation of tauro‐β‐muricholic acid (TβMCA), a natural antagonist of the farnesoid X receptor (FXR) that is involved in the regulation of BA and glucose metabolism. CAP‐induced suppression of enterohepatic FXR‐fibroblast growth factor 15 (FGF15) signaling contributes to the increased BA pool size, followed by increases in the expression of cholesterol 7α‐hydroxylase (CYP7A1) and hepatic BA synthesis. Additionally, depleting gut microbiota by antibiotics administration abolishes the beneficial effects of CAP on BA metabolism and glucose homeostasis. Conclusions: CAP‐induced improvements in BA and glucose metabolism are partially mediated by the gut microbiota‐BA‐enterohepatic FXR axis in db/db mice. Abstract : Capsaicin (CAP) administration markedly improves glucose tolerance and insulin sensitivity through decreasing gluconeogenesis and increasing glycogen synthesis in the liver. CAP significantly increases the accumulation of TβMCA by decreasing the abundance of the Lactobacillus genus and its BSH activity. The repression of enterohepatic FXR‐FGF15 signaling induced by the accumulation of TβMCA mediates the beneficial effects of CAP on glucose and bile acid metabolism.